Neue Leitbilder der Raumentwicklung: Ein Impuls zur Modernisierung der Raumordnung? - Sinz, Manfred; Aring, Jürgen (Raumforschung und Raumordnung | Spatial Research and Planning, 2006)
After an intensive discussion within the planning community as well as in the political area the Standing Conference of Ministers responsible for Spatial Planning has decided upon new visions and guidelines for spatial development in Germany. Its main topics are contributions of planning and regional policy to general social and economic tasks like “growth and innovation”, “guaranteeing public services” and “safeguarding natural resources” as well as “shaping cultural landscapes”. The paper wants to explain why the new guidelines indicate an innovative step for spatial planning at the federal level in Germany. The main messages are: The guidelines identify their goals and proposals for action not from a traditional territorial perspective using categories like agglomerations and rural areas. Instead the new strategies refer to prevailing economic, social and environmental challenges like regional competitiveness, demographic change and conflicts on land-use priorities. This signifies a paradigm shift from traditional equity-oriented interventions in favour of rural areas to a stronger emphasis on urban agglomerations and their metropolitan development potentials. The apparent or supposed shift led to continuing political and ideological discussions which are treated in this article.